The Index of Hero’s Power and Nobility in Shakespearean Tragedy Drama: A Semiotic Study - M. Yuseano Kardiansyah (TEKNOSASTIK, 2016)
This paper discusses a study that investigates the index of hero’s power and nobility in Shakespearean tragedy dramas. Here, the discussion focuses on two works authored by William Shakespeare: "Macbeth" and “Othello”. Objective of this study is to investigate the signs that give index of power and nobility in those two Shakespearean tragedy dramas. The study is done by analyzing Macbeth and Othello in the way of tracing the intrinsic elements or texts of them. All related dialogs and narrations (data source) in these dramas are analyzed in order to disclose the indexes of power and nobility in Shakespearean tragedy dramas. All analyses from each works are compared in order to determine if there are similar indexes or even distinction among those works in depicting the sense of power and nobility as Shakespearean dramas. As the result, it is found that these two dramas contain similar pattern of indexes that lead to the figuration of each hero’s power and nobility in the dramas.